Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Pemerintah Daerah Provinsi Lampung - Putri, Riri Septyaningrum; Fermansyah, Deki; Eliza, Any; Suharto, Suharto (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine financial performance based on the ratio approach of effectiveness, independence, and fiscal decentralization in the city of Bandar Lampung. This study uses a qualitative descriptive approach. The data used in this study are secondary data taken through BPKAD Bandar Lampung for the fiscal year 2008-2017. The results of this study indicate that the ratio of regional financial effectiveness on average is at 90.49% with the effective category and the trend of regional financial effectiveness at 70.814%; The ratio of regional financial independence average is at 27.96% which is categorized as low and the trend of regional financial independence is at 262.42%; while the regional financial fiscal decentralization ratio on average was at 17.85% with the unfavorable category and the regional financial fiscal decentralization trend was at 197.23%.